Web reference decay: Passing the HTTP errors instead of quality information - Dundannanavar, Akshaykumar; Hadagali, Gururaj S. (AWARI, 2024)
Web resource links routinely fail, and the content of links might change suddenly and without notice. When referrals to online sites offer proof or supporting data, these web dynamics are harmful. Any hyperlink’s final content is susceptible to two phenomena: the link breaks (link rot) and the content changes from its original state (content drift). The combination of both effects is referred to as reference rot. This paper aims to determine the application of online citations, the number of lost web citations, and the process of recovering missing web citations through the application of the Internet Archive’s Wayback Machine. According to the analysis, the Webology journal published 428 research articles between 2004 and 2020 that had 2,273 online citations. There are 1,260 (55.43%) accessible web citations out of the mentioned ones, whereas 1,013 (44.57%) are missing. There are 1,856 (81.65%) active web citations, up from 1,260 (55.43%) after an effort was made to retrieve 596 lost web citations using the Wayback Machine tool. That meant that the overall increase of the active URLs was 26.22%. The article presents a method for creating specific collections for online archiving in the future, even though web-archiving tools now take snapshots of websites in real time. The paper recommends that future curation standards for real-time web archiving shall include platform dynamics and cultural variations in link-sharing habits.